Assessment of backfat thickness and its relationship with reproductive performance of sows – preliminary findings - Motaung, Thabang Godfrey; Osotsi, Joab Malanda; Gashew, Mequanint; Ndunguru , Sawadi F.; Novotni-Danko , Gabriella (Acta Agraria Debreceniensis, 2024)
Backfat thickness (BFT) is an important trait that influences reproductive performance in sows. This study investigated the relationship between sow BFT at farrowing and the number of live born (LB), stillborn (SB), and Mummies (Ms) in different parities (P) (1, 2, 3, 4, 5, 6, 7 and 8). Backfat thickness was measured at point P2 (BFT at the last rib, at the junction of the thoracic and lumbar vertebrae 3–5 cm from the midline of the spine (mm). In total, 216 sows were measured on day 109 of gestation (when they entered farrowing). Descriptive statistics showed that the mean BFT was 14.55 mm SEM 0.171 SD 2.576. Parity had a significant effect on BFT, with a Kruskal-Wallis chi-squared value of 22.728 (df = 7, p = 0.002). Post-hoc pairwise comparisons using Dunn's test in R revealed that P1 exhibited a significantly higher BFT than P3 (p = 0.001) and P4 (p = 0.025). Spearman’s correlation coefficient indicated a very weak negative relationship between BFT and LB, whereas there was a strong relationship between BFT and SB and Ms. However, the correlations were not significant p>0.05. This finding suggests that assessing the BFT before farrowing is a helpful tool for guiding sow management and pig production. Additionally, these findings offer data that can be used to inform culling policies.